Justice as Fair Division - Bartrum, Ian C. (2018)
The current hyperpoliticization of the Court grows out of a feedback loop between politicized appointments and politicized decision-making. This Article suggests a change in the internal procedures by which the Court hears and decides particular cases. A three-Justice panel hears and decides each case. Appeal to an en banc sitting of the entire Court would require a unanimous vote of all non-recused Justices. This Article explores several possible approaches in selecting the three-Justice panel. This Article proposes that applying a fair division scheme to the Court's decision-making process might act to reverse this loop and work to depoliticize the Court over time